Paphiopedilum myanmaricum, a new species of slipper orchid (Cypripedioideae, Orchidaceae) - Koopowitz, Harold; Iamwiriyakul, Prapanth; Laohapatcharin, Srisuda (Phytotaxa, 2017)
A distinctively different and new species of Paphiopedilum Pfitzer belonging to subgenus Brachypetalum (Hallier) Pfitzer is described from Myanmar. Cribb (1998) enumerates only four species. Since then Govaerts & Cribb (2017) itemize seven species with an additional two varieties. This subgenus is confined to mainland South-east Asia extending from Thailand and Malaysia into Indochina and south-east China. It is not surprising, then that an additional species should also be found in neighboring Myanmar.